The Concept of Provision in the Holy Quran (A Semantic - Exegetical Study) - Younis, Asmaa Wajeh (Journal of Islamic Sciences, 2025)
This study aims to reveal the true meaning of the word "rizq" (sustenance) according to linguists and terminologists, and to outline the most important types and categories related to it. This study also includes an explanation of the formulation of the concept of rizq (sustenance) in the Quran, including context, past tense, present tense, and imperative verbs, and an explanation of each meaning separately according to its occurrence in the verses.This research sheds light on a novel study focusing on semantics in its literal, rhetorical, and exegetical aspects, concerning the root meaning of "sustenance" and its derivatives. After meticulous analysis, it was found that the number of Quranic verses and chapters containing the term "sustenance" and its derivatives amounts to 109 verses in 44 chapters, including 32 Meccan chapters and 12 Medinan ones. This study, therefore, focused on several key aspects, all of which employ semantics, rhetoric, and exegesis to accurately define this concept in the Quran. The study benefited from other semantic approaches, which highlighted the relationship between the signifier and the signified, as well as the social, intellectual, and psychological reflections resulting from this relationship, derived from the internal structure of the term, which is the subject of this study. Semantics and rhetoric can serve as fundamental bases for developing new terms and expressions that keep pace with intellectual, social, and psychological changes, both for individuals and societies as a whole. However, this aspect has only been sparsely explored by linguists and authors of Arabic and other lexicons.
Keywords: semantics; sustenance; linguistic root; context